First report of wasabi mottle virus causing ringspot and vein-clearing symptoms on wasabi (Wasabia japonica) in North America. Issue 2 (4th March 2021) - MacDonald, Jesse L.; Punja, Zamir K.; Xiang, Yu; Bouthillier, Michael J.; Reade, Ron; DeYoung, Robyn M.; Bhagwat, Basdeo; Betz, Emily C.; Li, Ying Q.; Chen, Xiaoban
Abstract: Symptoms of ringspots and vein-clearing were observed on wasabi ( Wasabia japonica (Miq) Matsum) plants in three greenhouses in British Columbia during 2017. Ten indicator plant species, including four Nicotiana species, were inoculated with sap extracts from symptomatic leaves; after 4–11 days, necrotic lesions developed on all plants. Transmission electron microscopy revealed rod-shaped virions, 250–300 nm in length, in leaves of N. occidentalis and N. clevelandii . Total RNA from symptomatic wasabi tissues was used in RT-PCR with universal primers corresponding to five virus genera and specific primers for turnip ringspot virus and alfalfa mosaic virus. Amplicons ~400 bp in size were obtained with tobamovirus primer set TobN up3/TobN do4 and amplicons of ~300 and ~600 bp were obtained with ilarvirus primer set Ilar1F5/Ilar1R7. Sequencing and MegaBLAST (NCBI) query of the Ilar amplicons showed 99% identity to wasabi mottle virus (WMoV), a member of the genus Tobamovirus . Next-generation Sequencing confirmed WMoV as the only virus present in diseased plants. BC isolates (GenBank accession no. MK431779) showed 99.43% sequence identity to isolate 'Alishan' (GenBank accession no. KJ207375.1) and 98.62% identity to 'Tochigi' strain (GenBank accession no. AB017504.1). Mechanical inoculation of wasabi cultivars 'Green Thumb' and 'Daruma' produced ringspots and vein-clearing symptoms after 22–23 days on the former while the latter was asymptomatic, but WMoV was detected in all plants by RT-PCR. WMoV may have been introduced into Canada on imported infected 'Green Thumb' plants and subsequently spread through commercial vegetative propagation. The effects on yield or rhizome quality are yet unknown.